Методичні підходи до оцінювання ефективності підготовки робітничих кадрів - Орлова, А. А.; Orlova, А. (КНТУ, 2011)
У статті розглядається проблема оцінки ефективності підготовки робітничих кадрів, досліджуються існуючі методики проведення оцінки ефективності підготовки робітників та їх недоліки. Надано рекомендації щодо створення комплексної методики оцінки ефективності підготовки робітників. The article considers the problem of assessing the effectiveness of workers’ training, the existing methods for evaluating the effectiveness of workers’ training and their shortcomings are investigated. Recommendations for the establishment of integrated methodology for assessing the effectiveness of workers’ training are provided.
Methodological approaches to evaluating the effectiveness of workers’ training
Keywords: робітничі кадри; оцінка ефективності підготовки робітничих кадрів; економічна ефективність; соціальна ефективність